PENGARUH BUDAYA ORGANISASI DAN KERJASAMA TIM TERHADAP KINERJA KARYAWAN PADA PT. HADJI KALLA TOYOTA CABANG URIP SUMOHARJO MAKASSAR - Akbar Said; Muh. Reski Iskandar (Universitas Ichsan Sidenreng Rappang, 2024)
The performance of an employee is evaluated based on how successfully they perform the assigned tasks according to the established standards. The purpose of this study is to (1) untangle the relationship between corporate culture and employee output and (2) hide the relationship between teamwork and output in the workplace. Primary data were obtained from employees at PT. Hadji Kalla Toyota, Urip Sumoharjo Makassar Branch. A sample size of 54 respondents was used to calculate the sample size using the slovin technique. The traditional hypotheses of normality, multicollinearity, and heteroscedasticity were investigated to ensure the validity and dependability of the results obtained from the questionnaire. Multiple linear regression analysis and SPSS 23, which is a statistical package specifically designed for social sciences, were used in the data analysis process. Statistics showing that organizational culture and work teams have a good influence on employee performance provide credence to all these assumptions, which are supported by statistics